Government subsidies and corporate disclosure - Huang, Ying (Journal of Accounting and Economics, 2022)
Government subsidies allocated by politicians are ultimately funded by taxpayers, who care about how tax money is spent and demand transparency. I argue that subsidized firms, as beneficiaries of government subsidies, have incentives to provide more disclosures to help politicians achieve a reputation for transparency as well as to lower their own costs from public scrutiny. Using a novel dataset that tracks government subsidies, I provide the first large-sample evidence on the relation between government subsidies and firm disclosure. I find that relative to unsubsidized firms, subsidized firms provide more voluntary disclosures of general information about their business activities and profitability, as well as more disclosures of subsidy-goal-related information, such as job creation and capital investment. Further, these associations are stronger for firms operating in or obtaining subsidies from states whose politicians reveal a stronger preference for subsidy transparency, and for firms that are more likely to attract public scrutiny.